The South Shetland and South Orkney Islands with the tracks of the several discoverers 1819 to 1843 - Walker, J. (kaivertaja); Walker, C. (kaivertaja) (London, 1887)
Kartta kuuluu A. E. Nordenskiöldin kokoelmaan Large corrections 1884, April 1887